Critical Review on Improving the Claim Management Process in Malaysia - Bakhary, Nor Azmi; ., Azmi Ibrahim; ., Noor Akmal Adillah Ismail (Journal of Education and Vocational Research, 2013)
Claims for additional costs and time extensions result from a variety of events occurring during the course of construction. To enhance the chances of success, contractors when submitting their claims must closely follow the steps stipulated in the contract conditions, by providing a breakdown of alleged additional costs and time with sufficient documentation. This paper aims to provide a better insight on the process of claims management in the Malaysian construction industry. It is reviewing the early part of the PhD research and hopefully the findings will try to generate means of improving the claims management process. With the proper claim management framework, it is hoped that contractors can utilize it to improve their claim management process in the future.